Evaluation of the Cytotoxic Activity of Citrinin on Human Prostate Cancer Cell Lines - Yuce, Hande; Ozek, Dilan Askin; Unuvar, Songul (Wiley, 2025)
[Abstract Not Available]
Keywords: Citrinin; Cytotoxic activity; L929; PC-3